Perspectives of Region XI Head Start Federal, Research, and Program Partners in Carrying out a National Study of American Indian and Alaska Native Head Start Children, Families, and Programs. Issue 1 (23rd August 2021) - Sarche, Michelle; Malone, Lizabeth M.; Hoard, Laura; Barnes‐Najor, Jessica; Cameron, Ann; West, Jerry; Barofsky, Meryl; ,
Abstract: The American Indian and Alaska Native Head Start Family and Child Experiences Survey (AIAN FACES) 2015 was the first national study of children served by Region XI Head Start programs, which are those operated by federally recognized AIAN tribes. Until 2015, Region XI programs had not been included in national studies of Head Start children's experiences and development, leaving them without this critical source of data to inform policy and practice as is available to other Head Start regions. To address this gap, four groups of stakeholders gathered to plan for a study that put the needs of Region XI Head Start at the forefront, was informed by the historical context of research with AIAN communities, and was guided by community psychology and community‐based and tribal participatory approaches. Engaged partnership is a common practice in research with AIAN communities, but rarely on a national scale across diverse communities. The study's success speaks to the success of the unique national partnership between the Region XI Head Start, research, and federal stakeholders who formed the AIAN FACES Workgroup. This first‐person account documents the perspective of each group as they undertook this seminal effort and reviews connections with, and lessons learned for, the broader field of community psychology. Highlights: AIAN Head Start programs have not been represented in any of the research on Head Start to date. Without data, Head Start policy and practice decisions are not fully informed. Research with AIAN communities must be informed by community priorities and protocols for research. Four stakeholder groups, including AIAN Head Start leaders, formed a Workgroup to address this gap. Each group's knowledge and expertise was critical to the study's success.